Factors Affecting the Effectiveness of Change Management: A case study for Hawassa Industrial Park - Paulos Manedo Hafebo; Ika Hartika (Britain International for Academic Research (BIAR-Publisher), 2024)
This study is aimed to show that to assess factors affecting the effectiveness of change management in Hawassa Industrial Park. The study employed primary source of information through questionnaire. The researcher used a simple random sampling for this selected specific topic in the study area. In data analysis perspective explanatory and confirmatory factor analysis (CFA) methods were used and model fit index was conducted to select good fit model by suing Structural equation Modeling’s (SEM) software of AMOS to analysis regression and confirmatory factors of variables. The questionnaire was distributed for 76 respondents and all questionnaires were responded. In the study the value of R Square was 0.684. This shows that 68.8 percent of the effectiveness of change management can be explained by the independent variables while, the remaining 31.6 percent of change management is influenced by other factors. Another major issue of the study was model fit indices and factor analysis. The study has a good model fit indices in majority of variables and almost all factors were selected for the study. Finally, a series of hypotheses are posited to explore the relationships of the variables. According to the findings of this study shows that change leadership, communication, employees’ engagement, and employees’ commitment employees’ empowerment have significant positive effect on effectiveness of change management. For this finding the researcher recommended as industry should emphasize on employees’ engagement through policy development that encourage employees’ engagement and participative decision as well as leadership training are needed to be practical responsibility of Hawassa Industrial Park.